Peran Twitter sebagai Cyberspace dalam Aksi Gerakan Gejayan Memanggil - Andreas, Ronald; Erviantono, Tedi; Jayanthi Mertha, AA. Sg. Mirah Mahaswari (Jurnal Nawala Politika; Vol 1 No 1 (2022): Jurnal Ilmu Politik 2022, 2022)
Gejayan Memanggil movement through #GejayanMemanggil has become the strategy of the Aliansi Rakyat Bergerak in cyberspace and mobilize a simultaneous movement on the streets in September 22, 2019.The data of this research are in the form of discourse productions such as articles, posters, photos, tweets/opinions, to interviews with representative sources. In this study, strategies were found in the form of using personal accounts of alliance members or consolidation participants. ARB relies on the popularity of #GejayanMemanggil which is driven by a collective influence that is not involved in the political sphere as opposition or pro-government. Influencer stirred up the spirit of nationalism, political awareness, and calls to rise up, and make changes with the format of tweets, hashtags, memes, and videos. This movement targets young people, in this case Indonesian Student Component. Keywords : Gejayan Memanggil, Social Movement, Cyber-activism, Twitter